Arctic trophy hunters, tourism and masculinities, 1827–1914. (2nd July 2016) - Aarekol, Lena
ABSTRACT: Trophy hunting in the Arctic happened in an intersection between tourism, expeditions and hunting. This study contributes to a discrete history of masculinity within the context of trophy hunting organized from North Norway and to a broader understanding of Arctic masculinity. As trophy-hunting expeditions are primarily a male, even masculinist, practice, an analysis from a gender perspective is unavoidable. By taking an empirical approach I investigate performances of masculinity in written accounts of Arctic trophy-hunting expeditions from 1827–1914. The use of masculinity as a pivot demonstrates that a modification of the prevailing perception of Arctic masculinity is necessary. While the general understanding is dominated by an emphasis on physical strength, roughness, ingenuity, and self-realization, qualities connected to traditional knowledge of trappers, sailors and explorers, my analysis shows that trophy hunting introduced aristocratic ideals such as gentlemen's sport, self-discipline, hunting morals, care for nature and knowledge to their home communities. Trophy hunting made possible performances of different forms of masculinity, not only the conquest and mastery of nature, but also the interest in and care for nature. Women accompanied as family members and hunters, and took part in the hunt more than has been commonly noted.